Ethanolic Extract of Curcuma domestica Val. and Curcuma xanthorrhiza Roxb.: A Comparative Study In Vitro and In Silico Antibacterial Effect against Methicillin-Resistant Staphylococcus aureus - Nasution, Halimah Raina; Yuandani, Yuandani; Septama, Abdi Wira; Ernawati, Teni; Khairunnisa, Nur Aini; Nugraha, Sony Eka; Sufitni, Sufitni; Utami, Dinda Sari (Trends in Sciences, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a priority pathogen due to its multidrug-resistant characteristics. This study compared the antibacterial, antibiofilm, bacteriolytic, and efflux pump inhibitory effects of Curcuma domestica and Curcuma xanthorrhiza rhizome extracts, both individually and in combination with tetracycline, against MRSA. Antibacterial activity and the combinatory effect with tetracycline were assessed using the microdilution method. Additionally, antibiofilm, bacteriolytic, and efflux pump inhibitory were investigated. Extracts from C. domestica and C. xanthorrhiza exhibited antibacterial effects against MRSA, with Minimum Inhibitory Concentration (MIC) values of 125 and 250 µg/mL, respectively. The combination of C. domestica and tetracycline demonstrated a synergistic interaction, with a Fractional Inhibitory Concentration Index (FICI) of 0.5. In contrast, the combination C. xanthorrhiza and tetracycline showed only an additive effect, with an FICI of 0.6. Computer simulations indicated that bisdemethoxycurcumin exhibited the strongest binding affinity to the protein inhibiting topoisomerase ATPase. Furthermore, when combined with tetracycline, each extract was effective in inhibiting biofilm formation and efflux pump activity in MRSA. This combination also induced cell death by altering membrane permeability. The combination of Curcuma extracts with tetracycline demonstrated enhanced antibacterial activity against MRSA compared to the extracts used alone. HIGHLIGHTS Bisdemethoxycurcumin has the strongest binding affinity to the protein that inhibits topoisomerase ATPase with computer simulations The ethanolic extract of Curcuma xanthorrhiza has additive interaction with tetracycline against MRSA and revealed higher antibacterial activity, antibiofilm, bacteriolytic activity, and inhibit the efflux pump as compared to the extract alone. The combination of domestica extract and tetracycline produced a synergistic effect and reduced the MIC value of tetracycline against MRSA up to 1/32 MIC. GRAPHICAL ABSTRACT